Diaphragm movement sensor for phrenic nerve monitoring during cryoballoon procedures: the first clinical evaluation - Schemoul, Elsa; Tovmassian, Lilith; Mancini, Julien; Koutbi, Linda; Biermé, Cédric; Deharo, Jean-Claude; Franceschi, Frédéric; Maille, Baptiste (Frontiers in Cardiovascular Medicine, 2024)
Background and aims: Right phrenic nerve palsy is the most frequent complication of cryoballoon procedures. The SMARTFREEZE™ console (Boston Scientific, St. Paul, MN, USA) has integrated a new tool for diaphragm monitoring -the Diaphragm Movement Sensor; however, it has not been evaluated in clinical practice. We aimed to assess the diagnostic performance of the Diaphragm Movement Sensor based on compound motor action potential data recorded simultaneously.Methods: Thirty consecutive patients (mean age 63.2±10.2 years) were included. We simultaneously recorded the compound motor action potential and the Diaphragm Movement Sensor during cryoapplications in the right pulmonary veins. The right phrenic nerve was paced at 60 per minute, 12 V and 2.9 ms. Compound motor action potential monitoring with a 30% decrease cutoff for the diagnosis of phrenic nerve threatening was considered the gold standard. The Diaphragm Movement Sensor decrease threshold was also set at 30%.Considering compound motor action potential monitoring, phrenic nerve threatening occurred 11 times (in seven patients) among 84 cryoapplications (13.1%) at the right pulmonary veins. The sensitivity and specificity of the Diaphragm Movement Sensor were, respectively, 33% (95% CI 7-70%) and 49% (95% CI 38-61%; P<0.001). The predictive positive and negative values for the Diaphragm Movement Sensor were, respectively, 7% (95% CI 2-20%) and 86% (95% CI 72-95%). The Diaphragm Movement Sensor gave an erroneous diagnosis in 44/84 cryoapplications (52.4%).The diagnostic performance of the Diaphragm Movement Sensor is low, and the relevance of its use in clinical practice may be debated.